Таежный фаунистический комплекс млекопитающих Северной Америки в сравнении с евразиатским таежным комплексом - Кулик, И.Л. (Вестник зоологии, 1975)
The species composition of the typical mammals of the American taiga complex is analysed and its specificity is shown. It is established that the centre of the distribution area of the typical species of this complex is in the Canadian plains located southwards of the Great Slave Lake and northwords of the Great Lakes. The comparison of the American and Eurasian taiga complexes of mammals showed a relative slight similarity of their species composition that gives reasons to consider the territories of their distribution to be independent zoogeographical regions.